2001
DOI: 10.1002/1521-4125(200102)24:2<119::aid-ceat119>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Macroscopic Elongational Flow on Dispersion Processes in Agitated Tanks

Abstract: The influence of elongational and shear gradients in the macroscopic flow field in agitated tanks on dispersion processes is investigated. Measurements of droplet size distribution for a liquid‐liquid dispersion process using phase‐Doppler anemometry (PDA) reveal that axial‐flow impellers, such as the 24°‐pitched‐blade turbine and propeller, produce smaller droplets than the Rushton turbine at the same average specific power and energy input. These results stand in contradiction to the usual assumption that on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…25 However, the studies in particulate systems reveal that the particle stress caused by these impellers is higher. 13,14,26,28,36 This statement is in general agreement with the results of the present study with the exceptions of PBT-6×45°and PROPRing-h/d=0.33. The interpretation of the increased hydromechanical stress caused by axial impellers was proven to be challenging.…”
Section: Industrial and Engineering Chemistry Researchsupporting
confidence: 93%
See 2 more Smart Citations
“…25 However, the studies in particulate systems reveal that the particle stress caused by these impellers is higher. 13,14,26,28,36 This statement is in general agreement with the results of the present study with the exceptions of PBT-6×45°and PROPRing-h/d=0.33. The interpretation of the increased hydromechanical stress caused by axial impellers was proven to be challenging.…”
Section: Industrial and Engineering Chemistry Researchsupporting
confidence: 93%
“…Most frequently, dispersion processes in stirred tanks are performed under turbulent flow conditions. 12,13 The stress acting on particles is determined by the local turbulent velocity fluctuations over time u 2 ′ . Additionally, if there is a significant density difference between the two phases, that is, bulk fluid and particles, the mean velocities of the particles and the fluid also differ, which leads to impact stress.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluid flow data for the bulk liquid can be measured by using contactless and contacting measurement techniques which are e.g. particle image velocimetry [ 26 , 28 , 29 ], laser doppler anemometry [ 30 ] and hot film anemometer [ 31 ]. In short, the complete 3D characterization of fluid flows in stirred bioreactors requires measurement techniques that are difficult, highly sophisticated and very time-consuming [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wille et al [46] described the effect of macroscopic elongational flow on the emulsification in stirred tank. They showed that axial flow impellers yielded smaller droplets than their radial counterparts.…”
Section: Batch Wise Emulsification: Stirred Vesselmentioning
confidence: 99%